Removal characteristics of dissolved organic matter and membrane fouling in ultrafiltration and reverse osmosis membrane combined processes treating the secondary effluent of wastewater treatment plant - Jianwei Liu (IWA Publishing, 2021)
The widespread implementation of municipal wastewater treatment and reuse must first ensure the safety of reused wastewater. The effluent of the municipal wastewater treatment plant contains a large amount of dissolved organic matter (DOM), which adversely affects the reuse of wastewater. In this study, the ultrafiltration (UF) + reverse osmosis (RO) process was used to treat the secondary effluent from wastewater treatment plants. The relationship between the removal performance, membrane fouling of the UF + RO process, and DOM removal characteristics of influent were studied. The results show that DOM can be removed effectively by UF + RO process. The UF mainly removes DOM with a molecular weight greater than 10 kDa, while RO has a significant removal effect on low-molecular-weight DOM, which mainly causes UF and RO membrane fouling. The UF + RO process has a significant removal rate on fulvic acid, humic acid, tyrosine, and tryptophan, and the order is humic acid > fulvic acid > tyrosine > tryptophan. Fulvic acid contributed the most to the UF membrane fouling, while fulvic acid and protein-like proteins contributed mainly to the RO membrane fouling.